PENGARUH LABEL HALAL TERHADAP KEPUTUSAN PEMBELIAN MASYARAKAT DALAM MEMILIH TEMPAT MAKAN DI KOTA PEKANBARU : (STUDI KASUS MASYARAKAT MUSLIM KOTA PEKANBARU) - jamilah, putri; sayhrullah, M. Syahrullah; Sulfy Sri Rasmy Polem (JURNAL ISLAMIKA, 2023)
The halal label is halal information or evidence contained in every product that will be consumed by the public, in accordance with the provisions of Islamic law and legislation issued by the MUI. Having a halal label gives Muslims a sense of trust and caution when consuming food. Therefore, this research aims to find out how the halal label influences people's purchasing decisions in choosing a place to eat in Pekanbaru city. This research uses a quantitative method using a simple linear regression method. The population in this research is the Muslim community of Pekanbaru city of 5,622,998 people and a sample of 270 people using the simple random sampling method. Data collection used a questionnaire with data processing using the SPSS 26.0 analysis tool. The research results show a tcount value of 27.864, which means tcount > ttable of 1.969 with a significance level of 0.000<0.05, which means Ho is rejected and Ha is accepted, which means that there is a positive and significant influence between the halal label on people's purchasing decisions.